Níveis de pressão sonora e uso das rotas de leitura e escrita em escolares de Santa Maria - Santos, Juliana Feitosa dos (2012)
The purpose of this dissertation was to understand the possible relationships among exposure to high sound pressure levels, auditory processing, and performance in the routes of reading and writing, having in mind that children who are acquiring such abilities, into an improper acoustic environment, have tendency to have writing processing difficulties. In this context, this investigation was conducted through the integration among the knowledge of Acoustics, Audiology, and Neuropsychology in the acquisition of writing language. The accomplished procedures were acoustic measures, auditory evaluation, which include the inspection of the external auditory canal, vocal and pure-tone audiometry, imitanciometry, and for the auditory processing, the Staggered Spondaic Words (SSW) test was performed. The writing evaluation included reading and writing isolated words to analyze the use of the lexical and phonological routes. The results of the acoustic measurements through the dosimeter in four schools in Santa Maria, RS, Brazil divided the sample of 87 children of 3 and 4 years old of primary school, aged eight to ten years, into two groups exposed (17 children) and not exposed (70 children) to levels higher than 80dB(A). The sample with normal auditory threshold was also separated in groups with 38 children without changes in acoustic immittance measurements and 49 with changes. The results showed that the children who were exposed to high sound pressure levels are damaged to use the lexical and phonological routes in reading and writing, even if such alterations were not evidenced with significant differences in the auditory processing test, between the exposed and not exposed groups. It is possible to infer, however, that the noise affects the reading and writing processing, and preventive actions are necessary to avoid trouble to the students related to their academic and social abilities.